Queer : the ultimate LGBT guide for teens - Belge, Kathy; Bieschke, Marke (Zest Books, 2011)
"A guide that helps LGBT teens come out to friends and family, navigate their new LGBT social life, figure out if a crush is also queer, and rise up against bigotry and homophobia."
Keywords: homosexualita; gayové; lesbismus; bisexualita; transsexualismus; homosexuality; gay men; lesbianism; bisexuality; transsexualism; publikace pro mládež; juvenile literature